Validity of a Sham Dry Needling Technique on a Healthy Population - Daniel M Cushman; Anna Holman; Lee Skinner; Keith Cummings; Peter Haight; Masaru Teramoto (International Journal of Sports Physical Therapy)
# Background Various methods of sham procedures have been used in controlled trials evaluating dry needling efficacy although few have performed validation studies of the sham procedure.